Effects of rice husk as a precursor on crystallization kinetic of glass ceramics derived from 45S5 bioglass? - Leenakul W. (2014)
The crystallization kinetic of glass ceramics derived from 45S5 Bioglass ? made from rice husk ash was studied. In order to investigate and control the sintering process of these samples, the crystallization kinetic of the major phase was studied by differential scanning calorimetry (DSC) in the range of 700- 800 C and temperature-time-transformation (TTT) curves were established. Differential thermal analysis (DTA) was performed to investigate the thermal parameters of the prepared glasses. Phase evolution of the glass-ceramics sintered at temperatures ranging between 600 and 900 C was investigated by Scanning electron microscope (SEM) and X-ray diffraction (XRD) techniques. All thermal parameters (the first glass transition temperature; Tg1, the softening point; Ts, the crystallization temperature; Tc and the second glass transition temperature; Tg2) of the prepared glass containing rice husk precursor were found to be lower than that of the controlled glass. It was found that the major crystalline phase in all sintered samples was Na2Ca2Si3O9. ? Springer-Verlag Berlin Heidelberg 2013.